MODAL SOSIAL PADA KELEMBAGAAN JIMPITAN KOMUNITAS PETANI SAWAH TADAH HUJAN DESA MARGA KAYA - Siti Mariyani (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2023)
The current institutional challenges of jimpitan are causing the jimpitan institution to experience upheaval, namely the crisis persists or begins to fade. The fading or survival of the jimpitan institution is inseparable from the social capital of the farming community. This study aims to determine social capital in the rain-fed farming community's jimpitan institution in Marga Kaya Village. The research method is in-depth interviews with selected informants by purposive sampling. The data analysis used was descriptive qualitative. The research activities were carried out in January-April 2019. The research location was chosen purposively, namely Marga Kaya Village, Jati Agung District, South Lampung Regency. Social capital in the Jimpitan institutional community of rainfed rice farmers in Marga Kaya Village is seen from three things, namely trust, norms and networks. Networking, namely connecting between farmers by communicating and conveying information regarding jimpitan activities as well as networking with outside communities such as within the Rukun Tetangga (RT) and village level. The norm is that there are rules that apply, such as the schedule for taking jimpitan at night during night patrols and the form of jimpitan in the form of rice or money according to the agreement of each Rukun Tetangga (RT). Trust is seen in jimpitan management activities by the RT head and administrators which are then used for the benefit of the common people.